How do teachers support their students on the autism spectrum in Australian primary schools?. Issue 1 (2nd July 2019) - Clark, Megan; Adams, Dawn; Roberts, Jacqueline; Westerveld, Marleen
Abstract : This study investigated the supports and modifications made available to students on the autism spectrum in Australian schools. Teachers rated the importance of several factors in determining the grades of their students and reported on the frequency of student engagement with a range of instructional materials. Eighty‐seven teachers identified the modifications, accommodations and additional assistance provide to primary school students on the autism spectrum. Teachers also compared the frequency of class engagement and methods of evaluating outcomes for students with and without autism. A range of modifications and adjustments were implemented to support students on the spectrum. There were no significant differences in the frequency of instructional material use of students on the autism spectrum compared to their classmates. However, teachers did report differences in their methods of determining the grades of their students with and without autism. This is an important first step in understanding the experiences of teachers who are educating students on the autism spectrum in Australian schools. The findings reveal that teachers are working to support the diverse learning needs of their students on the autism spectrum. Further investigation of the factors that are driving teachers' use of school‐based supports is warranted.